Strengthening the Indonesian Bicameral Parliament: Siyasah Dusturiyah Perspective - Kosasih, Ade; M, Sirajuddin; Fauzan, Fauzan; Kusmidi, Henderi (AL-ISTINBATH : Jurnal Hukum Islam, 2024)
This research aims at finding a strategy to strengthen Indonesia's bicameral parliament. It is a parliamentary system consisting of an Upper House and a Lower House. The Upper House, Regional Representative Council (DPD), Â represents certain groups or regions, and the Lower House, House of Representatives (DPR), represents national interests. Ideally the position of the DPR and DPD is in an equal position, however the DPD arrangements in the constitution have a power but do not reflect the bicameral principle. If left unchecked, it can trigger regional dissatisfaction which threatens the disintegration of the nation. This research employed normative juridical research methods with a conceptual and statutory approach. The result showed that the DPD has made efforts to strengthen it through al-sutha al tasyri'iyah (formal amendments) but failed. Moreover, the DPD has also carried out legal reviews by the Constitutional Court (judicial review) but the results have not been significant. The most realistic way to strengthen the DPD and has never been used before is through a constitutional political strategy (siyasah dusturiyah) to create constitutional conventions by vetoing draft laws whose decisions are made without involving the DPD. Therefore, the Indonesian parliamentary system can run in the double check system and check and balance paradigm in maintaining democracy and regional autonomy. Thus, if the DPD has a strong bargaining position in parliament then the goal of forming a strong bicameral parliament can be established.